Commanding Nature by Obeying Her: A Review Essay on Joel Mokyr's A Culture of Growth - Enrico Spolaore (Center for Economic Studies and ifo Institute (CESifo), 2019)
Why is modern society capable of cumulative innovation? In A Culture of Growth: The Origins of the Modern Economy, Joel Mokyr persuasively argues that sustained technological progress stemmed from a change in cultural beliefs. The change occurred gradually during the seventeenth and eighteenth century and was fostered by an intellectual elite that formed a transnational community and adopted new attitudes toward the creation and diffusion of knowledge, setting the foundation for the ethos of modern science. The book is a significant contribution to the growing literature that links culture and economics. This review discusses Mokyr's historical analysis in relation to the following questions: What is culture and how should we use it in economics? How can culture explain modern economic growth? Will the culture of growth that caused modern prosperity persist in the future?
Keywords: N13; N33; O30; O52; Z10; 330; technological progress; innovation; useful knowledge; cultural change